Morphodynamic modelling of a gravel beach at the NW Portuguese coast - Gomes, A. (2018)
Besides exhibiting an erosion trend for decades, the NW coastal zone of Portugal, since the end of 20th century, was the stage of a new phenomenon. Between Lima and Cávado rivers, previously dissipative, sandy beaches transformed in mixed sand-gravel beaches with gravelly beach cusps (by the end of 80?s) and progressively convert in entire reflective gravel beaches (since 2000), though maintaining the inherited dune systems on their backshore. This beach is being monitored since 2013 using DGPS, aerophotogrametic surveys and expedite gravel size characterization. Based on these monitoring results a modeling work was carried out to simulate the beach morphodynamics, applying XBeach-G software. The model was able to simulate the beach morphodynamics.